Applications of Aptamers in Medicine: A Mini Review (Bangladesh Pharmaceutical Journal, 2017)
Aptamers are single-stranded DNA or RNA molecules that bind to its target with high affinity and specificity. Nucleic acid aptamers are an attractive class of carrier molecules because of their tissue penetration capability, high chemical flexibility, low immunogenicity, low toxicity and cost effective production. These characteristics make aptamers an alternative to the antibody. An aptamer can be developed for the treatment of age-related macular degeneracy disease, blood clotting, cancer and auto-immune diseases etc. Macugen is so far the only aptamer-based drug that received FDA approval. Cancer patients are treated by targeting two proteins named nucleolin and CXCL12. Targeted delivery of aptamers has been successfully developed that reduce the occurrence of the unwanted off-target effects. Aptamers are susceptible to renal filtration and endonuclease cleavage. Conjugation with PEG or cholesterol and chemical modification can decrease renal clearance and increase serum stability.Bangladesh Pharmaceutical Journal 20(1): 99-104, 2017